2016
DOI: 10.1186/s13005-016-0104-2
|View full text |Cite
|
Sign up to set email alerts
|

Precision of fibula positioning guide in mandibular reconstruction with a fibula graft

Abstract: BackgroundThis study examined the usefulness of the fibula positioning guide for boosting the accuracy of mandible reconstructions.MethodsThirty mandibular rapid prototype (RP) models were allocated to experimental (N = 15) and control (N = 15) groups. For reference, we prepared a reconstructed mandibular RP model with a three-dimensional printer, based on surgical simulation. In the experimental group, a fibula positioning guide template and fibula cutting guide, based on simulation, were used to reconstruct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Lim et al reported that the maximum error was observed in the condylar region when only a fibula-cutting guide was used ( 27 ). This error was thought to be related with the movement of the condylar head in the TMJ ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lim et al reported that the maximum error was observed in the condylar region when only a fibula-cutting guide was used ( 27 ). This error was thought to be related with the movement of the condylar head in the TMJ ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al reported that the maximum error was observed in the condylar region when only a fibula-cutting guide was used ( 27 ). This error was thought to be related with the movement of the condylar head in the TMJ ( 27 ). They suggested that it may be more helpful to adjust the anterior-posterior position of the fibular bone by referring to the 3D model rather than using a cutting guide ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…17 Current advances in 3D imaging, navigation system, CAD/CAM techniques, STL models, and RP techniques allow reconstructive surgery to be performed rapidly and accurately. 3,[17][18][19] In soft tissue surgery, navigation-guidance may not provide optimal results because of the problem of tissue drifting, but this is not an issue in hard tissue surgery. 17 Nevertheless, whereas robotic surgery has been used for the soft tissue free flap reconstructions, 20,21 its application in craniomaxillofacial bone defect reconstructions is still a novelty.…”
Section: Discussionmentioning
confidence: 99%
“…The use of 3-dimensional (3D) imaging and a 3D digitized mesh in plastic surgery enables the acquisition of objective data and facilitates pre-and postoperative evaluation of malformations, sequelae of trauma and tumors, and orthognathic surgery. In addition, the 3D mesh facilitates guide production with virtual planning and 3D printing [1]- [6], quantification of results after aesthetic surgery [7]- [9], and simulation of volume changes [10]- [16]. Furthermore, digital files may be transmitted easily, enabling file exchange for remote evaluation and wider potential for the clinical use of the 3D mesh [17].…”
Section: Introductionmentioning
confidence: 99%